2019
DOI: 10.3389/fpsyt.2019.00806
|View full text |Cite
|
Sign up to set email alerts
|

Use of Technology to Promote Child Behavioral Health in the Context of Pediatric Care: A Scoping Review and Applications to Low- and Middle-Income Countries

Abstract: Background: The burden of mental, neurological, and substance (MNS) disorders is greater in low- and middle-income countries (LMICs). The rapid growth of digital health (i.e., eHealth) approaches offer new solutions for transforming pediatric mental health services and have the potential to address multiple resource and system barriers. However, little work has been done in applying eHealth to promote young children’s mental health in LMICs. It is also not clear how eHealth has been and might be applied to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…[53][54][55] A systematic review showed promising effects on parenting of technology-based programs in low-and middle-income countries that focused on children's social-emotional behavior. 56 In contrast with these promising models in media-based intervention, there are serious public health challenges associated with the ongoing COVID-19 "infodemic" of misinformation. 57 An increase in the use of online platforms has increased children's risk to online threads, such as exposure to inappropriate content and exploitation.…”
Section: Volume 223 August 2020mentioning
confidence: 99%
“…[53][54][55] A systematic review showed promising effects on parenting of technology-based programs in low-and middle-income countries that focused on children's social-emotional behavior. 56 In contrast with these promising models in media-based intervention, there are serious public health challenges associated with the ongoing COVID-19 "infodemic" of misinformation. 57 An increase in the use of online platforms has increased children's risk to online threads, such as exposure to inappropriate content and exploitation.…”
Section: Volume 223 August 2020mentioning
confidence: 99%
“…Conversely, the study revealed that a patient with a master's degree or higher was 2.297 times more likely to use eHealth technologies than the rest of the participants. Education influences eHealth adoption and many scholars have equally underscored the importance of education in accelerating eHealth technology acceptance and adoption [19], [41], [31], [67]. In a study conducted in Ghana, it was revealed that participants having a higher education used eHealth devices more often than their counterparts [56].…”
Section: Discussionmentioning
confidence: 99%
“…Given their interest, the development of customized smartphone apps may be promising direction for raising awareness of child mental health, delivering educational resources about child behavioral health, and increasing access to related services among an underserved Chinese immigrant community [22]. Patterns of eHealth use across a spectrum of individual/family and system level of eHealth interventions that can be applied to promote child mental health and strengthen mental health service systems [23]. Telemedicine is a technological tool that is improving the health of children around the world.…”
Section: Discussionmentioning
confidence: 99%